2021
DOI: 10.1002/ente.202100330
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Room‐Temperature Li||Ga–Sn Liquid Metal Battery for Grid Energy Storage

Abstract: Herein, a room‐temperature liquid metal battery (LMB) with a solid lithium anode electrode and gallium–tin (Ga–Sn) alloy cathode electrode is reported. With the improved wettability of the electric collector and grain‐refined liquid metal droplets cathode, the aforementioned LMB exhibits good cyclic reversibility and negligible self‐discharge. The result shows that the assembled Li||Ga–Sn battery has a satisfactory specific capacity (409 mAh g−1) and high energy efficiency (up to 92%). The low melting point Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In the Ga 3d spectrum, the peak around 17.9 eV is Ga 0 . In addition, the peak of Ga−O (20.3 eV) indicates the partial oxidation of eGaSn during the preparation process [16] . Furthermore, the X‐ray diffraction (XRD) patterns demonstrated that the prepared eGaSn NDs are amorphous (Figure 2i).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the Ga 3d spectrum, the peak around 17.9 eV is Ga 0 . In addition, the peak of Ga−O (20.3 eV) indicates the partial oxidation of eGaSn during the preparation process [16] . Furthermore, the X‐ray diffraction (XRD) patterns demonstrated that the prepared eGaSn NDs are amorphous (Figure 2i).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the peak of GaÀ O (20.3 eV) indicates the partial oxidation of eGaSn during the preparation process. [16] Furthermore, the X-ray diffraction (XRD) patterns demonstrated that the prepared eGaSn NDs are amorphous (Figure 2i). The FE-SEM image of eGaSn@TiO 2 (Figures 2c, S5) shows favourable dispersion and sphericity, because of the coating of eGaSn NDs with an approximately 6.5 nm-thickness amorphous TiO 2 layer (Figures 2d, e, S6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations